IS THIS TEXTBOOK TASK-BASED?: A TASK APPROACH TO THE PEDAGOGICAL ANALYSIS OF THE PRESCRIBED INDONESIAN ELT TEXTBOOK - Arif Rahmat; Rachel Joanna Hosea; Sri Yani (Siliwangi University, 2019)
In recent decades, the issues on Task-Based Language Teaching (TBLT) have been widely investigated across the globe (e.g., Japan, Greece, and Indonesia). TBLT facilitates learners to improve their communicative competence in a natural setting. Although TBLT is not a new issue in ELT, there remains empirical evidence how it is represented in an ELT textbook in Indonesia, in particular. To fill this gap, informed by TBLT framework (Nunan, 2004), the present study addresses to examine how speaking tasks are prescribed in an Indonesian Senior High School ELT textbook. The result of this study shows that although the textbook portrayed a TBLT, there should be a revisit in the tasks, because it is important to make the designed task connected to the real world.Therefore, this study implies for English teachers as curriculum remakers in relation to design and re-appropriate English materials from an ELT textbook by considering the proper task to implement in their English classrooms.